Induction of Haemophilus influenzae Type b Capsular Antibody in Neonatal Rabbits by Gastrointestinal Colonization with Cross-Reacting Escherichia coli - Myerowitz, Richard L. (1973)
In two separate experiments, newborn rabbits were fed a live suspension of either of two Escherichia coli strains which possess a “K” antigen cross-reactive with the capsular polysaccharide of Haemophilus influenzae type b. Both feedings were harmless and resulted in fecal excretion of the fed E. coli in most animals as well as active immunization of fed animals toward H. influenzae type b. Feeding non-enteropathogenic, cross-reacting E coli to newborns may be a method for inducing active immunity toward H. influenzae type b diseases by accelerating the acquisition of “natural” immunity.